References to Archival Materials in Scholarly History Monographs - Bronstad, Kris (Qualitative and Quantitative Methods in Libraries; Vol 6 No 2 (2017): June 2017 Issue, 2019)
This study examines citations of archival material in a sample of 136 recently-published scholarly historical monographs produced by a selection of highly-cited American university presses, with the goal of discovering patterns in scholarly user reportage of archival use. The study found that 68% of the titles referenced at least one archival collection, that archival collections housed at universities were used more often than other types of repositories, that citations to physical archival collections far outnumbered citations to digital archival collections and that the amount and type of of repositories did not in most cases vary based on historical subject matter of the book. The findings could potentially provide a baseline by which further and more diverse archival use and users can be measured .